KARAKTERISTIK KEBAKARAN PERMUKAAN GAMBUT BERBASIS LUASAN DESA MENURUT TIPE PENUTUPAN LAHAN DI KALIMANTAN - Irfan Malik Setiabudi; Wahyu Kusumaningrum (Jurnal Analisis Kebijakan Kehutanan, 2021)
Forest and land fires occur almost every year in Indonesia. They  dominantly befall in Sumatra and Kalimantan. Most of the fire incidents in Indonesia are caused by anthropogenic factors. Moreover, practices of land management  are indicated to have a strong relationship to the fires. Village-based fire control becomes one of approaches  applied by the government. This study is conducted to reveal relational characteristics between village-based land management practices and fire events, principally in peatland areas, with a focused area in Kalimantan. Practices of land management will be analised  by the characteristics of existing official land use, while fire events will be identified by the existence and intensity of hotspots. The method applied in this research is spatio-temporal analysis based on fire density analysis. Fire incidents occur from July to November, with the peak point occurrence is in September. Area in unmanaged land has increased the potency of fire events than in forest type and in other managed land cover types. Fires located in peatland also generate potential of fires significantly than in mineral land. Further, land cover and land type aspects together with village fire density can be employed as the priority in implementing policy on village-based fire control.